2010
DOI: 10.1075/is.11.2.01sha
|View full text |Cite
|
Sign up to set email alerts
|

The crying shame of robot nannies

Abstract: Childcare robots are being manufactured and developed with the long term aim of creating surrogate carers. While total child-care is not yet being promoted, there are indications that it is "on the cards". We examine recent research and developments in childcare robots and speculate on progress over the coming years by extrapolating from other ongoing robotics work. Our main aim is to raise ethical questions about the part or full-time replacement of primary carers. The questions are about human rights, privac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(105 citation statements)
references
References 53 publications
0
98
0
7
Order By: Relevance
“…Similar concerns have been raised about leaving children in the 'care' of robots to the extent that their attachments to humans are compromised (Sharkey and Sharkey 2010) but again there is no legislation or rights that explicitly prevent such a possibility, other than that associated with child neglect. There is an urgent need for something like a digital bill of rights to ensure that there is some protection from the situations that could arise if humans place robots in positions of power over humans.…”
Section: (I) Biological Machines Versus Mechanical Machinesmentioning
confidence: 99%
“…Similar concerns have been raised about leaving children in the 'care' of robots to the extent that their attachments to humans are compromised (Sharkey and Sharkey 2010) but again there is no legislation or rights that explicitly prevent such a possibility, other than that associated with child neglect. There is an urgent need for something like a digital bill of rights to ensure that there is some protection from the situations that could arise if humans place robots in positions of power over humans.…”
Section: (I) Biological Machines Versus Mechanical Machinesmentioning
confidence: 99%
“…Nevertheless, technology-driven ethical appraisals are not child-centered, and seldom take into consideration the possibility of detrimental effects on child development or the wider social context (e.g., the home or the school). In contrast, psychology-driven ethical appraisals such as outlined by Amanda and Noel Sharkey [45,46] do highlight issues of emotional attachment, deception of the child, and loss of human contact (see also [33]). Apropos teachers' attitudes to robots in the classroom, research reported in [47] demonstrates the exigency of taking the consideration of ethics beyond design issues and toward engagement with stakeholders' views on how robots may affect their current practices.…”
Section: How Could Biases Of the Technological Imagination Be Avoided?mentioning
confidence: 99%
“…As Sharkey and Sharkey discuss (Sharkey & Sharkey, 2010a), the sensitive response of a robot to a child in a way that establish a fixed and safe attachment is not a certain fact. Because infants' dependencies, firm attachment to a caregiver depends on good development.…”
Section: People's Concerns About Children and Robot Carementioning
confidence: 99%